2011
DOI: 10.1111/j.1523-1739.2011.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Varying Responses of Northeastern North American Amphibians to the Chytrid Pathogen Batrachochytrium dendrobatidis

Abstract: Chytridiomycosis, caused by Batrachochytrium dendrobatidis (Bd), is widespread among amphibians in northeastern North America. It is unknown, however, whether Bd has the potential to cause extensive amphibian mortalities in northeastern North America as have occurred elsewhere. In the laboratory, we exposed seven common northeastern North American amphibian species to Bd to assess the likelihood of population-level effects from the disease. We exposed larval wood frogs (Lithobates sylvaticus) and postmetamorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 34 publications
(40 reference statements)
10
88
0
Order By: Relevance
“…We chose American toad metamorphs in this study because they are sensitive to Bd in the laboratory (Gahl, Longcore, & Houlahan, 2012; Wise, Rumschlag, & Boone, 2014) and are infected with Bd in natural populations (Longcore, Longcore, Pessier, & Halteman, 2007; Richards‐Hrdlicka, Richardson, & Mohabir, 2013), which makes this species an ideal model organism for assessing variation in Bd isolates’ virulence across environmental conditions. We predicted that isolates from California and Panama would be more virulent than Ohio and Maine, having stronger effects on host growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…We chose American toad metamorphs in this study because they are sensitive to Bd in the laboratory (Gahl, Longcore, & Houlahan, 2012; Wise, Rumschlag, & Boone, 2014) and are infected with Bd in natural populations (Longcore, Longcore, Pessier, & Halteman, 2007; Richards‐Hrdlicka, Richardson, & Mohabir, 2013), which makes this species an ideal model organism for assessing variation in Bd isolates’ virulence across environmental conditions. We predicted that isolates from California and Panama would be more virulent than Ohio and Maine, having stronger effects on host growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been suggested that L. pipiens may be a ''carrier'' species (Woodhams et al 2008;Gahl et al 2011), as it is currently not known to exhibit acute symptoms or mortality when infected by Bd. In a recent study of an endangered population of L. pipiens in British Columbia, Bd is thought to have swept through in an epidemic fashion leading to rapid declines and endangerment of that population (Voordouw et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the wood frog L. sylvaticus can die from chytridiomycosis at young post-metamorphic stages under laboratory conditions (Searle et al 2011, Gahl et al 2012. We used bullfrogs and wood frogs as representative species with low and high mortality risk for chytridiomycosis, respectively.…”
Section: Introductionmentioning
confidence: 99%